The Influence of Social Media Marketing and Brand Awareness on Somethinc Product Purchase Intention - Dinda Andini (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
This study aimed to examine the effect of Social Media Marketing and Brand Awareness on the Purchase Intention of Somethinc products. The research employed a quantitative approach with a population consisting of individuals who were familiar with Somethinc products. The sample consisted of 104 respondents selected using a non-probability sampling method with purposive sampling technique. Data were collected through an online questionnaire and analyzed using multiple linear regression to test the partial and simultaneous effects among variables. The results showed that Social Media Marketing had a positive and significant effect on Purchase Intention. Brand Awareness also had a positive and significant effect on Purchase Intention. Furthermore, Social Media Marketing and Brand Awareness simultaneously had a positive and significant effect on the Purchase Intention of Somethinc products. These findings confirmed that effective social media–based marketing strategies and high Brand Awareness could increase consumers' Purchase Intention. This research provided practical contributions for cosmetic companies, particularly Somethinc, in designing more targeted marketing communication strategies, as well as academic contributions to the development of literature related to digital marketing and consumer behavior.